A Glyoxalase-1 knockdown does not have major short term effects on energy expenditure and atherosclerosis in mice - Wortmann, Markus; Hakimi, Maani; Fleming, Thomas; Peters, Andreas; Sijmonsma, Tjeerd P.; Herzig, Stephan; Nawroth, Peter Paul; Böckler, Dittmar; Dihlmann, Susanne (Journal of diabetes research, 2016)
Objective. Glyoxalase-1 is an enzyme detoxifying methylglyoxal (MG). MG is a potent precursor of advanced glycation endproducts which are regarded to be a key player in micro- and macrovascular damage. Yet, the role of Glo1 in atherosclerosis remains unclear. In this study, the effect of Glo1 on mouse metabolism and atherosclerosis is evaluated. Methods. Glo1 knockdown mice were fed a high fat or a standard diet for 10 weeks. Body weight and composition were investigated by Echo MRI. The PhenoMaster system was used to measure the energy expenditure. To evaluate the impact of Glo1 on atherosclerosis, Glo1KD mice were crossed with ApoE-knockout mice and fed a high fat diet for 14 weeks. Results. Glo1 activity was significantly reduced in heart, liver, and kidney lysates derived from Glo1KD mice. Yet, there was no increase in methylglyoxal-derived AGEs in all organs analyzed. The Glo1 knockdown did not affect body weight or body composition. Metabolic studies via indirect calorimetry did not show significant effects on energy expenditure. Glo1KD mice crossed to ApoE−/− mice did not show enhanced formation of atherosclerosis. Conclusion. A Glo1 knockdown does not have major short term effects on the energy expenditure or the formation of atherosclerotic plaques.
Published online 2015 December 15
Gesehen am 03.07.2020